Analysis of Potassium (K) Uptake and Plant Growth of Lettuce (Lactuca sativa L.): Effect of AB Mix Concentrations and NPK Fertilizer Doses - Ramlan Ramlan; Siti Hijrah; Adnan Khaliq (The University of Lampung, 2025)
Soil is a crucial growing medium that supplies nutrients essential for plant development. This study aimed to evaluate the effect of AB Mix concentrations and NPK fertilizer dosages on potassium (K) uptake, growth, and yield of lettuce (Lactuca sativa L.). The experiment was conducted from June to September 2024 in Nupabomba Village, Donggala Regency, and in the Soil Science Laboratory of Tadulako University, using a factorial Randomized Complete Block Design (RCBD). The first factor was AB Mix concentration: A0 (control), A1 (24 ml/3 L), and A2 (1,800 ppm = 27 ml/3 L). The second factor was NPK dosage: D0 (control), D1 (0.7 g/7 kg), and D2 (1.4 g/7 kg). Data were analyzed using ANOVA followed by the Honest Significant Difference (HSD) test at a 5% significance level. Results showed that AB Mix and NPK fertilizer significantly affected potassium content in plant tissue but did not significantly affect soil pH, C-organic content, soil potassium levels, or potassium uptake. Treatments significantly increased plant height, number of leaves, and fresh weight, while dry weight was unaffected. These findings indicate that appropriate AB Mix and NPK combinations enhance lettuce growth and yield by improving tissue potassium content without altering soil properties.